Cryptochrome Regulates Circadian Locomotor Rhythms in the Small Brown Planthopper Laodelphax striatellus (Fallén) - Jiang, Yan-Dong; Yuan, Xin; Zhou, Wen-Wu; Bai, Yue-Liang; Wang, Gui-Yao; Zhu, Zeng-Rong (Frontiers in Physiology, 2018)
Most living organisms have developed internal circadian clocks to anticipate the daily environmental changes. The circadian clocks are composed of several transcriptional-translational feedback loops, in which cryptochromes (CRYs) serve as critical elements. In insects, some CRYs act as photopigments to control circadian photoentrainment, while the others act as transcriptional regulators. We cloned and characterized two cryptochrome genes, the Drosophila-like (lscry1) and vertebrate-like (lscry2) genes, in a rice pest Laodelphax striatellus. Quantitative real-time PCR showed that lscry1 and lscry2 expressed ubiquitously from nymph to adult stages as well as in different tissues. The transcript levels of lscry2 fluctuated in a circadian manner. Constant light led to arrhythmic locomotor activities in L.striatellus. It also inhibited the mRNA oscillation of lscry2 and promoted the transcription of lscry1. Knockdown of lscry1 or lscry2 by RNA interference (RNAi) reduced the rhythmicity of L.striatellus in constant darkness, but not in light dark cycles. These results suggested that lscry1 and lscry2 were putative circadian clock genes of L. striatellus, involved in the regulation of locomotor rhythms.